2001 a space odyssey - Clarke, Arthur C. (London Hachette, 2001)
From the savannas of Africa at the dawn of mankind to the rings of Saturn as man ventures to the outer rim of our solar system, 2001: A Space Odyssey is a journey unlike any other.
Keywords: Twenty-first century--Fiction.